Integration of business intelligence system and managment information systems : an open-source approach - Beghman, Behbudov (2016)
If we look at over past years, Business Intelligence (BI) and Management Information System (MIS) became unavoidable technological advantages that bring financial benefits to large companies which could purchase, implement and maintain the MIS and BI solutions. But small companies have limited budgets that can make unachievable the implementation of such systems because they cannot support, in general, the total cost of these solutions. In this context, open source software has the capability to reduce costs, providing the software industry with an alternative and competitive way of doing business, contributing to reduce the competitive disparity between large and small size enterprises. This document explores an open source (OS) approach to integration of BI and MIS, taking into account that open source software can be an alternative option to the commercial solutions where the most important factor for this purpose is cost saving. In other hand, we present a research indicating that the integration of these systems can be a promising and desirable solution for small sized enterprises where the cost saving is an issue.